Parasitic parameters extraction of InP HBT only from S-parameters measured under cut-off and normal bias conditions. (November 2022) - Qi, Junjun; Lu, Hongliang; Zhao, Ranran; Yan, Silu; Cheng, Lin; Zhang, Yuming
Highlights: All the extrinsic parameters are determined by employing S-parameter measured only under cut-off and normal bias conditions. The scaling rule for the intrinsic base-emitter capacitance and the parameter scanning method for the base–collector extrinsic capacitance are used to obtain all capacitance parameters. The extrinsic inductances and resistances are obtained by the direct extraction method. Finally, these more accurate parasitic values are used as the initial values for parameter optimization, and the optimal parasitic parameter values are obtained by fine-tuning. The proposed method not only eliminates the critical measurement of the open-collector condition, but also greatly improves the efficiency and accuracy of parameter optimization. Abstract: An improved parasitic parameters extraction method for InP heterojunction bipolar transistor (HBT) is developed. The difference between this method and previous methods is that all parasitic parameters can be extracted by relying only on the S-parameters measured under the cut-off and normal bias conditions. All the capacitance parameters in the equivalent circuit at the low-frequency cut-off can be extracted by combining the analytical closed formulas and the parameter scanning method. The intrinsic resistance R bi is obtained indirectly by extracting the extrinsic resistance R e based on the Z-parameter method in the normal bias conditions. By de-embedding the parasitic capacitances, all the values of parasitic inductances and extrinsic resistances are obtained by the direct extraction method under the cut-off condition. The proposed method not only eliminates the critical measurement of the open-collector condition, but also greatly improves the efficiency and accuracy of parameter optimization. For different sizes and bias conditions of InP HBT devices, the excellent agreement between simulated and measured results is verified all over the frequency range of 0.4–50 GHz.